Calculation of magnetic coupling constants with hybrid density functionals - Mansikkamäki, Akseli (2013)
The currently available computational methods for the calculation of magnetic coupling constants with density functional theory have been reviewed. These methods include modern approximations to the exchangecorrelation functional, such as hybrid, range-separated and double-hybrid functionals, as well as approaches to treat the severe spin symmetry problems encountered in density functional calculations of magnetic interactions. In addition to the commonly used unrestricted Kohn–Sham formalism, density functional methods based on multireference wave functions and ensemble densities are also discussed. Performance of these models based on various studies has been summarized. The results indicate that self-interaction error plays an important role in the performance of density functional methods and is responsible for many of their shortcomings. If the self-interaction error and problems related to spin symmetry are treated in a theoretically correct manner, density functional theory can offer a very good description of magnetic coupling constants.